Use of External Fixators as a 3-Dimensional Navigation Drill Guide for Arthroscopic Ankle Arthrodesis - Park, Young Uk (Biomed Res Int, 2020)
In this article, we describe a novel technique using external fixators and cannulated screws to construct a 3-dimensional navigation drill guide to predict the screw trajectory before screw insertion that can prevent screw collision during arthroscopic ankle arthrodesis. Four orthopedic residents who had no prior experience of ankle arthrodesis were instructed on how to use the 3-dimensional navigation drill guide and where to insert the screws for ankle arthrodesis. Each resident inserted 6.5 cannulated screws on 8 sawbone ankle models using the device and the C-arm fluoroscopy. An experienced attending surgeon also inserted the same screws on 2 sawbone ankle models to find out if there is any difference between the experienced and inexperienced surgeons. All four residents and an attending surgeon did not experience any collision of screws for the three cannulated screws. Notably, one resident had collision of the 4th screw on his first sawbone model. On the second saw bone model, all surgeons could insert 5 screws without redrilling. A 3-dimensional navigation drill guide constructed with external fixators can assist surgeons in implementing percutaneous screws for arthroscopic ankle arthrodesis.